2018
DOI: 10.1136/gutjnl-2018-317297
|View full text |Cite
|
Sign up to set email alerts
|

Faecal immunochemical tests (FIT) versus colonoscopy for surveillance after screening and polypectomy: a diagnostic accuracy and cost-effectiveness study

Abstract: ObjectiveThe English Bowel Cancer Screening Programme (BCSP) recommends 3 yearly colonoscopy surveillance for patients at intermediate risk of colorectal cancer (CRC) postpolypectomy (those with three to four small adenomas or one ≥10 mm). We investigated whether faecal immunochemical tests (FITs) could reduce surveillance burden on patients and endoscopy services.DesignIntermediate-risk patients (60–72 years) recommended 3 yearly surveillance were recruited within the BCSP (January 2012–December 2013). FITs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 44 publications
1
49
0
Order By: Relevance
“…Several studies report on the long-term performance of FIT-based population screening programmes for CRC, but evidence for surveillance after polypectomy is lacking in these studies. One study reports on participants recruited between January 2012 and December 2013 via the English BCSP 92. Men and women aged 60–72 years, deemed at intermediate-risk following adenoma removal after a positive guaiac faecal occult blood test, were offered quantitative FIT at 1, 2 and 3 years post-polypectomy.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies report on the long-term performance of FIT-based population screening programmes for CRC, but evidence for surveillance after polypectomy is lacking in these studies. One study reports on participants recruited between January 2012 and December 2013 via the English BCSP 92. Men and women aged 60–72 years, deemed at intermediate-risk following adenoma removal after a positive guaiac faecal occult blood test, were offered quantitative FIT at 1, 2 and 3 years post-polypectomy.…”
Section: Resultsmentioning
confidence: 99%
“…A study found that the incidence and mortality of colon cancer have gradually increased in recent years (Bray et al, 2018). The current diagnostic strategies for colon cancer mainly include biopsy, laboratory examination, and colonoscopy (Cross et al, 2019;Kawamura et al, 2019). Therefore, establishing a reliable risk assessment model is urgently needed to assess the survival prognosis of patients with colon cancer and optimize clinical treatment decisions.…”
Section: Introductionmentioning
confidence: 99%
“…We read with interest the article by Cross et al ,1 which examined the use of FIT in intermediate risk patients undergoing 3 yearly surveillance colonoscopies. The investigators assessed the diagnostic accuracy of this approach, together with the number of advanced adenomas and colorectal cancers missed, and the potential cost savings.…”
mentioning
confidence: 99%